From the Trenches: Louvain to the Aisne, the First Record of an Eye-Witness - Young, Geoffrey Winthrop, 1876-1958 (Salt Lake City, UT : Project Gutenberg, 2022)
"From the Trenches: Louvain to the Aisne, the First Record of an Eye-Witness" by Geoffrey Winthrop Young is a historical account written in the early 20th century. This book provides firsthand insights and observations of the early days of World War I, detailing the chaos and upheaval experienced in Paris, Brussels, and beyond as the war escalated. The narrative chronicles the experiences of a war correspondent as he navigates the rapidly changing landscapes and the emotional turmoil of those caught in the conflict. The opening of the book introduces the reader to the author's return from a climbing trip, only to find himself plunged into the impending war as he volunteers as a war correspondent for the Daily News. Young's observations reflect a deep sense of shock and disbelief as he travels from England to Paris amidst a backdrop of panic and mobilization. Initial encounters with soldiers and civilians ahead of the German advance illustrate the sense of vulnerability and uncertainty in the air, setting the stage for the grim realities soon to come. The author captures the profound human experience of war, blending personal anecdotes with broader observations about society's disintegration as it confronts the brutal force of conflict. (This is an automatically generated summary.)
Release date is 2022-01-04
Graeme Mackreth and The Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: World War, 1914-1918 -- Personal narratives